Recursos terapêuticos físicos no tratamento de lesões por pressão em pacientes com lesão medular: uma revisão sistemática - SANTOS, Emmanuele Celina Souza dos (2021)
Introduction: Physical therapeutic resources include phototherapy, electrotherapy and thermotherapy, being commonly described in the literature for promoting positive results. in tissue repair in pressure injuries, which result from tissue necrosis caused by ischemia when external pressure is applied for a prolonged period on the skin. Spinal cord injury is a risk factor for its development. Objective: Synthesize the evidence of interventions of therapeutic resources that can be used as adjuvant in the management of wound healing in pressure injuries in individuals with spinal cord injury. Methods: This is a systematic review performed in Pubmed, Lilacs, Cochrane, Pedro and Google Scholar with articles published between 1991 and April 2020, in Portuguese and English, using the descriptors: “Low level light therapy”; “Therapy ultrasonic”; “High voltage electrical stimulation”; “Radiofrequency Therapies”, “Ultraviolet Therapies” and “Microcurrent Therapy”, following the PRISMA guideline. Results: Were nineteen studies were included, among which eight resources were identified, such as: Laser therapy, LED, Ultrasound, high and low voltage electrical stimulation, Radiofrequency, Ultraviolet C and Microcurrent. Discussion: The found resources have been shown to be effective in healing pressure injuries in individuals with spinal cord injury. The application technique and intervention time vary according to the characteristics of the wounds, taking into account the aspect of the edge and bed and, mainly, dimension and stage of the lesion. Conclusion: Laser therapy and high-voltage electrical stimulation presented better results in healing rate in relation to tissue repair time, when compared to the other selected features.